Wheelchair outcome measurement instruments for children: a scoping review protocol. - Curi, Haidar Tafner; Ferretti, Eliana Chaves; de Soárez, Patrícia Coelho (Disability & Rehabilitation: Assistive Technology, 2024)
Purpose: The proposed scoping review aims to explore and map wheelchair outcome measurement instruments for children in the literature. Method: The proposed scoping review will be conducted in accordance with the Joanna Briggs Institute (JBI) methodology. The review question and eligibility criteria were developed using the PCC (population, concept, context) mnemonic as follows: (P) children manual or motorised wheelchair users (aged ≤ 18 years), (C) wheelchair outcome measurement instruments, (C) primary sources of literature. The search will be conducted in nine relevant electronic databases. including grey literature from Academic Google. Study screening, selection, and data extraction will be performed independently by two authors. A third reviewer will resolve discrepancies between the authors. General characteristics, population, feasibility, interpretability data will be extracted in accordance with the COSMIN methodology (Consensus-based Standards for the selection of health Measurement Instruments). This will encompass data pertaining to the measurement properties of the domains of reliability, validity and responsiveness. A descriptive analysis will be carried out, and the results will be classified into categories and presented in tables accompanied by a descriptive summary. Results: The results can inform future research directions, clinical practice and the development of wheelchair outcome measurement instruments. Furthermore, it will help professionals in rehabilitation and wheelchair services to find the wheelchair outcome measurement instruments according to the target population and cultural context. IMPLICATIONS FOR REHABILITATION: This review has the potential to enhance understanding of wheelchair outcome measurement instruments, thereby enabling rehabilitation professionals to assess the impact and progress of wheelchair use within the target population. The findings related to measurement properties may guide future research in the field of wheelchair outcome measurement instruments. Additionally it will assist clinical professionals in identifying appropriate wheelchair outcome measurement instruments based on the target population and cultural context